Numeracy Competence: The Main Key to Culinary Students' Work Readiness Facing the Industrial World - Hidayatul Fitri; Lismi Animatul Chisbiyah; Marsono (Didaktika: Jurnal Kependidikan, 2024)
Numeracy competency plays a vital role for culinary arts students in facing the evolving challenges in the industry, especially in the data-driven era. As much as students must hone their cooking skills, culinary arts and management students are expected to be able to manage budgets, cost estimation, data management, and interpretation that will improve the decision-making process. However, many culinary schools focus on the practical work required in the kitchen, while the provision of numeracy skills is sometimes neglected. This article examines the relevance of numeracy competency in culinary students’ employability through a number of reports on related studies. The findings of the analysis indicate that there is a gap between the level of numeracy skills required by the industry and the skills possessed by culinary students. In this regard, curriculum updates are needed to create a balance between the practice and teaching of numeracy skills and the application of numerical technology. Methods such as problem-based learning (PBL) and utilizing restaurant management software can develop these skills in culinary students, preparing them for the dynamics of the rapidly changing culinary industry.